PEMBELAJARAN TEKS BERITA KELAS VII B MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Sukmawati, Perna Diana; Priyadi, Antonius Totok; Heryana, Nanang (Universitas Tanjungpura, 2024)
The purpose of this study is to explain the preparation, execution, and learning outcomes of news texts for grade VII B students utilizing the Problem Based Learning teaching methodology. The research is carried out in two cycles, each involving planning, acting, observing, and reflecting using a descriptive version of Class Action Research (PTK). The data for this study was collected from all grade VII B students at SMP Negeri 1 Simpang Hilir, North Kayong Regency, during the even semester of the 2023/2024 academic year. This study's data gathering approaches include observation and testing. This study generates planning in cycles I and II that are tailored to the module, as well as implementation tailored to the module that was created. The learning results of news readings for grade VII B students utilizing the Problem Based Learning methodology have improved. In the first cycle, students received an average score of 78.04 in the good category (B) for a knowledge evaluation conducted using written text group assignments delivered in the form of LKPD. Then, in cycle II, the average student score climbed from 78.04 in cycle I to 85 good category (B) with an assessment of knowledge and abilities utilizing group discussions and class presentations.